2019
DOI: 10.3389/fchem.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis of Ruthenium Nanoparticles and Polyoxometalate Integrated Within Single UiO−66 Microcrystals for Boosting the Efficiency of Methyl Levulinate to γ-Valerolactone

Abstract: The synthesis of heterogeneous cooperative catalysts in which two or more catalytically active components are spatially separated within a single material has generated considerable research efforts. The multiple functionalities of catalysts can significantly improve the efficiency of existing organic chemical transformations. Herein, we introduce ruthenium (Ru) nanoparticles (NPs) on the surfaces of a metal–organic framework pre-encapsulated with polyoxometalate silicotungstic acid (SiW) UiO−66 (University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…More specifically, a one-pot synthesis was performed to include the [CoW12O40] 6− anion in the size matching cage of ZIF-8 (see Figure 13). During the Besides this increase in stability after the embedding of the POM in a MOF support, several groups have demonstrated the mutual activation of the POM guest and MOF support [32,119,127]. A very special and extreme example of such a synergism was demonstrated in the work of Kögerler et al [128].…”
Section: Electrocatalysismentioning
confidence: 96%
“…More specifically, a one-pot synthesis was performed to include the [CoW12O40] 6− anion in the size matching cage of ZIF-8 (see Figure 13). During the Besides this increase in stability after the embedding of the POM in a MOF support, several groups have demonstrated the mutual activation of the POM guest and MOF support [32,119,127]. A very special and extreme example of such a synergism was demonstrated in the work of Kögerler et al [128].…”
Section: Electrocatalysismentioning
confidence: 96%
“…Additionally, Ru-H 4 SiW/MOF (M=Zr) catalysts were designed for the tandemhydrogenation/lactonization of ML to γ-valeroacetone . [122] The catalyst shows high activity and selectivity towards the desired product over five successive catalytic cycles.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%
“…The studies suggest that the balance of hydrogenation and hydrolysis, accordingly the acid/metal ratio, plays a crucial role in the optimization of the conversion and yield. Additionally, Ru‐H 4 SiW/MOF (M=Zr) catalysts were designed for the tandemhydrogenation/lactonization of ML to γ‐valeroacetone [122] . The catalyst shows high activity and selectivity towards the desired product over five successive catalytic cycles.…”
Section: Supported Hpasmentioning
confidence: 99%
“…Extensive studies on conversion of carbohydrate such as glucose and fructose to LA have been reported (Scheme 1). [17][18][19][20] The hydrogenation of LA into GVL with extra hydrogen source was performed in liquid-phase, gaseous-phase or supercritical CO2 systems by using different metal-based catalysts, such as Pd, Ru, Pt, Rh, Ni, Cu, Al. [5,10,14] Recently, formic acid, as a biomass derived, has been regarded as a material of hydrogen storage, which can be easily decomposed to molecule hydrogen at room temperature by catalytic conversion.…”
Section: Introductionmentioning
confidence: 99%